2014
DOI: 10.2754/avb201483s10s3
|View full text |Cite
|
Sign up to set email alerts
|

Growth and enterotoxin production of Bacillus cereus in cow, goat, and sheep milk

Abstract: The aim of this study was to compare Bacillus cereus growth rates and diarrhoeal enterotoxin production in raw and pasteurized goat, sheep, and cow milk in terms of storage conditions. Milk samples were inoculated with B. cereus (CCM 2010), which produces diarrhoeal enterotoxins. Enterotoxin production was tested by ELISA (Enzyme-Linked Immunosorbent Assay), and the count of B. cereus was determined by the plate method. With raw cow milk, B. cereus growth and enterotoxin production can be completely suppressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…B. cereus grows at temperature range from 4 to 50 °C and the optimum for growing is from 25 to 37 °C (Bhunia, 2008). Maximal growth (100%) of B. cereus was observed at 30 °C for 48 hours in raw milk (Montanhini et al 2013) and multiplication of B. cereus in pasteurized milk at 8, 15 and 22 °C (Necidová et al, 2014). Our results confirmed the growth and multiplication at 22 °C and also at 30 °C in accordance with above mentioned studies.…”
Section: Growth Of Bacteriasupporting
confidence: 91%
“…B. cereus grows at temperature range from 4 to 50 °C and the optimum for growing is from 25 to 37 °C (Bhunia, 2008). Maximal growth (100%) of B. cereus was observed at 30 °C for 48 hours in raw milk (Montanhini et al 2013) and multiplication of B. cereus in pasteurized milk at 8, 15 and 22 °C (Necidová et al, 2014). Our results confirmed the growth and multiplication at 22 °C and also at 30 °C in accordance with above mentioned studies.…”
Section: Growth Of Bacteriasupporting
confidence: 91%
“…Results observed by Tribst et al () also showed a long period of time (up to 10 days) for sheep milk to reach unacceptable bacterial counts under refrigeration. Necidová et al () demonstrated that Bacillus cereus growth was slower in sheep milk at 22 °C when compared with cow and goat milk, but it was not possible to establish whether this difference was related to intrinsic characteristics of sheep milk or different bacterial counts and types between the studied sources of milk. The continuous arrow in Figure shows that 8.4 h was needed to reach the count limit established by EU (1.5 × 10 6 cfu/mL).…”
Section: Resultsmentioning
confidence: 99%
“…In the European Union (EU), the limit for the total bacterial count (TBC) for small ruminant milk is 1.5 × 10 6 cfu/mL for manufacturing pasteurised milk products (Directive 94/71/EC ). Due to the milk composition and the high pH and A w , microbial growth may occur rapidly in raw milk (Necidová et al ). However, the high immunological activity of sheep milk may delay microbial growth after milking (Ramos and Juarez ).…”
Section: Introductionmentioning
confidence: 99%
“…While vegetative B. cereus cells can mainly be eliminated by mild heat treatment [146], spores are able to survive high temperatures, such as pasteurization or spray drying of milk [147]. Due to this survival and adjacent outgrowth of the competing microflora, growth of B. cereus occurs more often in pasteurized than in raw milk [145,148,149]. It has also been observed that spores from mesophilic strains survive food processing and heat treatment better than spores from psychrotrophic strains [150].…”
Section: Prevalence and Survival Of B Cereus In Foodsmentioning
confidence: 99%
“…A further, unneglectable factor is the competing microflora. Inactivation of germination and growth of B. cereus has been shown in fermented milk or slurries, Brie and Gouda cheese by different lactic acid bacteria-also described as biopreservation-in combination with low a w and Eh values, high salt content, low lactose content, aeration and high acidity [143,145,148,149,179,197,[200][201][202][203][204][205][206][207]. Next to food acidification, the microflora contributes to nutrient depletion for the pathogen [208,209].…”
Section: Prevalence and Survival Of B Cereus In Foodsmentioning
confidence: 99%